2014
DOI: 10.18632/oncotarget.1973
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the methylated CpG sites of paired box 5 (PAX5) promoter for prediction the prognosis of gastric cancer

Abstract: Paired box gene 5 (PAX5), a member of the paired box gene family, is involved in control of organ development and tissue differentiation. In previous study, PAX5 promoter methylation was found in gastric cancer (GC) cells and tissues. At present study, we found that the inconsistently methylated levels of PAX5 promoter were identified in the different GC tissues. The methylated CpG site count and the methylated statuses of four CpG sites (-236, -183, -162, and -152) were significantly associated with the survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Akaike information criterion (AIC) of different variables in a Cox proportional hazard regression model was calculated to quantify the corresponding prognostic prediction abilities. A small AIC value indicated a good model for predicting outcomes [12]. The significance was set at p \ 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Akaike information criterion (AIC) of different variables in a Cox proportional hazard regression model was calculated to quantify the corresponding prognostic prediction abilities. A small AIC value indicated a good model for predicting outcomes [12]. The significance was set at p \ 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…6 PAX5, located at chromosome 19p13, was originally identified as a B-cell-specific transcription factor required for B-cell differentiation 7 and neural development. 8 PAX5 gene methylation has been reported in various neoplasms, including HNSCC, 5 gastric cancer, 9 hepatoma, 10 breast cancer, and lung cancer. 11 PAX5 is also mutated in human acute B-cell leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a role in neural development and spermatogenesis. PAX5 gene methylation has been reported in various neoplasms including HNSCC(11), gastric cancer(12), hepatoma(13), breast cancer and lung cancer(14). In hepatocarcinogenesis, Liu et al, revealed that PAX5 directly binds to the p53 promoter and regulates p53 signaling.…”
Section: Introductionmentioning
confidence: 99%